Investigation of Ascaris lumbricoides Egg Morphology and Transmission Dynamics in the Iraqi Population - Mohammed Jasim Shakir (Diyala Journal of Medicine, 2025)
Background: Ascaris lumbricoides remains a significant public health concern, especially in settings with poor sanitation. Prevalence, transmission dynamics, and knowledge at the population level can inform the implementation of enhanced control. This study establishes the infection rate of A. lumbricoides in the Iraqi population, investigates factors associated with sociodemographics contributing to infection, and explores diversity in egg morphology